Pengaruh Penggunaan Platform Quizizz Terhadap Partisipasi Kelas dalam Pembelajaran Mufradat - Dewi, Annisa Rahmawati; Alawiyah, N. Lalah; Raswan, Raswan (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This study aims to reveal the impact of the Quizizz platform on enhancing classroom participation in Mufradat learning. The focus of this research is on the issue of low student participation in Mufradat learning at MI Al-Mursyidiyah Pamulang, which is often perceived as boring and uninteresting. This study employs a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. Data were collected through observation, documentation and classroom participation questionnaires. The research subjects consisted of 32 students from class six B of MI Al-Mursyidiyah. Data analysis was conducted using the "t-test" formula to evaluate the effect of the Quizizz platform on improving classroom participation in Mufradat learning. The t-test results showed a  value of 18.797 with a degree of freedom (df) of 31, while the  values were 2.0395 at a 5% significance level and 2.744 at a 1% significance level. These results indicate thatis greater than  at5% and 1% significance levels, with a P-value < 0.001. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning that the use of the Quizizz platform has a significant impact on improving classroom participation in Mufradat learning.